Probable Oil and Gas Reserves and Shareholder Returns: The Impact of Shale Gas - Bård Misund; Petter Osmundsen (Center for Economic Studies and ifo Institute (CESifo), 2015)
Oil and gas reserves are the most important assets of oil and gas companies. A source of confusion for investors in oil companies is that reserves quantities and values are uncertain estimates. Reserves are typically classified according to probabilities of recovery from underground reservoirs. All U.S. listed companies have to disclose proved reserves but not probable reserves, thus leaving out potentially important information for investors and financial analysts. This study addresses the impact on market valuation of various classifications of reserves amounts. Using a data sample of 94 companies that do disclose information on probable reserves, we compare the relation between three classifications of reserves and oil company returns. While we find that information on probable reserves do not have an impact on stock returns measured over the entire time period, this is not the case since 2009, coinciding with the onset of the shale gas revolution.
Keywords: Q33; Q35; G12; 330; oil and gas reserves; probably reserves; value relevance; accounting figures